- #1

IniquiTrance

- 190

- 0

[tex]\sum_{j=1}^n \sum_{k=1}^n a_{ik}b_{kj} = \left(\sum_{j=1}^n b_{kj}\right) \left(\sum_{k=1}^n a_{ik}\right) = 1\cdot 1 = 1[/tex]

Thanks!

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter IniquiTrance
- Start date

- #1

IniquiTrance

- 190

- 0

[tex]\sum_{j=1}^n \sum_{k=1}^n a_{ik}b_{kj} = \left(\sum_{j=1}^n b_{kj}\right) \left(\sum_{k=1}^n a_{ik}\right) = 1\cdot 1 = 1[/tex]

Thanks!

- #2

- 22,178

- 3,316

What you could do is:

[tex]\sum_{j=1}^n\sum_{k=1}^n a_{ik}b{kj}= \sum_{k=1}^n \sum_{j=1}^n a_{ik}b_{kj} = \sum_{k=1}^n \left(a_{ik} \sum_{j=1}^n b_{kj}\right)= \sum_{k=1}^n a_{ik}=1[/tex]

- #3

IniquiTrance

- 190

- 0

Thank you very much. I knew I wasn't understanding something.

Share:

- Replies
- 2

- Views
- 131

- Last Post

- Replies
- 3

- Views
- 955

- Last Post

- Replies
- 6

- Views
- 2K

- Last Post

- Replies
- 3

- Views
- 905

- Replies
- 1

- Views
- 2K

- Last Post

- Replies
- 3

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 2K

- Replies
- 9

- Views
- 1K

- Last Post

- Replies
- 5

- Views
- 5K